2012 International Conference on Privacy, Security, Risk and Trust and 2012 International Confernece on Social Computing 2012
DOI: 10.1109/socialcom-passat.2012.41
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ego Network Structure in Online Social Networks

Abstract: Abstract-Results about offline social networks demonstrated that the social relationships that an individual (ego) maintains with other people (alters) can be organised into different groups according to the ego network model. In this model the ego can be seen as the centre of a series of layers of increasing size. Social relationships between ego and alters in layers close to ego are stronger than those belonging to more external layers. Online Social Networks are becoming a fundamental medium for humans to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
92
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 26 publications
(53 reference statements)
12
92
0
Order By: Relevance
“…In the six communication systems examined in this study, the distributions of the strengths of social relationships d showed power law distributions (Fig. 1), similar to those observed in previous studies (Arnaboldi et al, 2012;Song et al, 2012;Fujihara and Miwa, 2014;Hossmann et al, 2011;Hu et al, 2012). Individuals selected social grooming partners in proportion to the strength of their social relationships, that is, the individuals tended to reinforce their strong social relationships; these power law distributions were generated by the Yule-Simon process (Yule, 1925;Simon, 1955;Newman, 2005) (Fig.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the six communication systems examined in this study, the distributions of the strengths of social relationships d showed power law distributions (Fig. 1), similar to those observed in previous studies (Arnaboldi et al, 2012;Song et al, 2012;Fujihara and Miwa, 2014;Hossmann et al, 2011;Hu et al, 2012). Individuals selected social grooming partners in proportion to the strength of their social relationships, that is, the individuals tended to reinforce their strong social relationships; these power law distributions were generated by the Yule-Simon process (Yule, 1925;Simon, 1955;Newman, 2005) (Fig.…”
Section: Introductionsupporting
confidence: 88%
“…O n the basis of the social brain hypothesis (Byrne and Whiten, 1989;Whiten and Byrne, 1997;Dunbar, 2000;Dunbar, 2003), an explanation of social structures, which are typical for humankind, is expected to offer knowledge about human origins, such as the limitation on the number of social relationships (Dunbar, 2000;Dunbar, 2003;Hill and Dunbar, 2003;Gonçalves et al, 2011;Arnaboldi et al, 2013a) and the skewness of social relationships (Zhou et al, 2005;Hossmann et al, 2011;Arnaboldi et al, 2012;Hu et al, 2012;Song et al, 2012;Arnaboldi et al, 2013b;Fujihara and Miwa, 2014), that is, its distributions following a power law (Hossmann et al, 2011;Arnaboldi et al, 2012;Hu et al, 2012;Pachur et al, 2012;Song et al, 2012;Fujihara and Miwa, 2014). These social structures may be caused by human beings' social grooming strategies (Dunbar, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem has recently received considerable traction as more and more social network data has been released publicly to enable social network data analysis [1]. Currently, the privacy of individuals and the confidentiality of data in social network data publishing are protected through variety anonymization techniques.…”
Section: Introductionmentioning
confidence: 99%